Epidemiological profile of hospitalizations and deaths due to amputations of limbs of people with Diabetes Mellitus in Alagoas – Brazil (Research, Society and Development, 2021)
This study aims to analyze the epidemiological profile of hospitalizations and deaths due to amputations of limbs of people with Diabetes Mellitus in the State of Alagoas. Ecological time series study with data obtained from the SUS Department of Informatics - DATASUS, whose main outcome is the number of admissions for amputation of limbs and deaths of people with Diabetes Mellitus, between 2007 and 2018, with variables related to person, time, place and intervention. Descriptive analysis, association measures and respective 95% confidence intervals were performed. 636 cases of amputation with 39 deaths were analyzed. There was an increase in amputations from 2014 to 2016; the mean age was 64 years of age with a range from one to 98 years. The lower limb amputation rate averaged 61%. Males present with a relative risk 37% higher risk of amputation due to diabetes than females and 101% of deaths. There is an 80% higher relative risk of death from amputation in the elderly than in non-elderly people. Actions by multiprofessional health teams in education, prevention and treatment programs fostering improved care interventions to prevent lower limb injuries can favor DM control by reducing amputations and deaths, as it is subject to monitoring, care and control that can be performed by primary health care.